PENERAPAN SISTEM INFORMASI MANAJEMEN DALAM PENGOLAHAN DATA PESERTA DIDIK DI MI NASRUL HAQ - Selvia Selvi Arfan; Muhammad Yaumi; Muhammad Yusuf T (Idaarah: Jurnal Manajemen Pendidikan, 2019)
Abstract: The purpose of this study are:1) To find out the implementation of the operational system of data processing of students by using a management information system in the Madrasah Ibtidaiyah Nasrul Haq Makassar. 2) To find out the data processing process of students in the Madrasah Ibtidaiyah Nasrul Haq Makassar. 3) To find out the impact of the use of management information systems on data processing of students in the Madrasah Ibtidaiyah Nasrul Haq Makassar.  The type of this study is a qualitative field research using data collection methods, namely interviews, observation and documentation. Data processing of students in Madrasah Ibtidaiyah Nasrul Haq based on management information systems is carried out using the online EMIS application, the process of data processing of students in the Madrasah Ibtidaiyah Nasrul Haq follows four main steps, namely data collection, data input, information storage and retrieval to be used and the use of management information systems in the management of student data in Nasrul Haq Ibtidaiyah Madrasah provides benefits in the form of ease of data storage, information retrieval processes, data security and access to student information wherever and whenever needed.